2014
DOI: 10.1675/063.037.0404
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success of the American Oystercatcher (Haematopus palliatus) in Texas

Abstract: The American Oystercatcher (Haematopus palliatus) is listed as a Species of High Concern in the United States Shorebird Conservation Plan due to a small population size and threats during its annual cycle. Previous studies of the American Oystercatcher have focused on Atlantic Coast populations; however, little is known about the reproductive success of the western Gulf Coast population. The objective of this study was to determine nest and brood survival of American Oystercatchers in Texas. A total of 337 nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Our observations from nest cameras and nest survival rates support a similar hypothesis for American white pelican nesting at Marsh Lake. In other colony‐nesting birds, the benefits of island nesting (Koczur et al , Anteau et al ) or nesting farther from mainland areas (Skorka et al ) are consistent with our findings for American white pelicans at Marsh Lake.…”
Section: Discussionsupporting
confidence: 90%
“…Our observations from nest cameras and nest survival rates support a similar hypothesis for American white pelican nesting at Marsh Lake. In other colony‐nesting birds, the benefits of island nesting (Koczur et al , Anteau et al ) or nesting farther from mainland areas (Skorka et al ) are consistent with our findings for American white pelicans at Marsh Lake.…”
Section: Discussionsupporting
confidence: 90%
“…Nests in this habitat were located at intermediate distances from the high tide line (< 30 m), suggesting a reduced risk of flooding as well as access to nearby foraging areas. Several studies of American Oystercatchers have revealed that those nesting on barrier islands with adjacent nesting and foraging territories have greater reproductive success (Koczur et al 2014). The greater breeding success of American Oystercatchers in the mixed marsh and dune habitat in our study may have been due to adults having more time to care for nests and broods than those in other habitats.…”
Section: Discussionmentioning
confidence: 99%
“…On the Atlantic coast, clutch sizes and breeding productivity varied from 2.3 to 2.7 eggs and 0.20 to 0.75 fledglings per pair, respectively (Wilke et al 2005, Traut et al 2006, Schulte and Simons 2015). Habitat suitability may also influence parental care by American Oystercatchers because of differences in food availability and the subsequent effects on breeding success (Koczur et al 2014, Schulte and Simons 2015). Moreover, adults that make shorter foraging trips defend and care for nests and chicks more than adults that travel longer distances to feed (Nol 1989, Koczur et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among 2 the factors affecting nest survival, nest predation has been shown to be the major cause of nest failure in most bird species (Ricklefs 1969, França et al 2016. For many species, nest survival varies over time (Grant et al 2005, Koczur et al 2014, Berkunsky et al 2016, França et al 2016, Polak 2016). Yet, studies evaluating the proximate factors involved in explaining nest survival, such as food, weather, and breeding activities of conspecifics, have mostly been carried out in temperate areas and rarely in the tropics (Thomson 1950, Martin 1987, Stutchbury and Morton 2008.…”
Section: Introductionmentioning
confidence: 99%